PERAN PUBLIC RELATION DALAM MENGEMBALIKAN CITRA PERUSAHAAN : STUDI KASUS APARTEMEN CINERE BELLEVUE SUITES PASCA KEBAKARAN TAHUN 2017 - FIRLY RACHMAH ISTIGHFARIN; MAGVIRA YULIANI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
After the fire that occurred at the Cinere Bellevue Suites apartment in 2017, thus the company's image and the level of trust of its residents had been impacted. Role of Public Relations played important position as the backbone of the company and as a key figure to restore the company's image. Companies with good images in the eyes of consumers, its products and services are relatively more acceptable to consumers. This research focuses on the role of Public Relations in restoring the image of the Cinere Bellevue Suites apartment post the fire that happened in 2017 by using a qualitative approach whereas researchers use informants as the primary data source. In addition, company data also becomes secondary data that supports this study. The results of this study indicate that there is a relationship with the theory used, namely the Adaptive Strategy theory and Image Restoration Theory. The theories states about adjustments to cases / issues that develop in companies experiencing a crisis that cannot be separated from the company's mistakes and negligence, all alone. Companies must have courage to admit mistakes and improve service quality and promises for better services. The company also made compromises, lobbied and negotiated with certain parties such as the victims by providing compensation, with the aim of getting the company's positive image back.